2008
DOI: 10.1007/s10295-008-0413-y
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of synthetic melanoidins-containing wastewater by a bacterial consortium

Abstract: The presence of melanoidins in molasses wastewater leads to water pollution both due to its dark brown color and its COD contents. In this study, a bacterial consortium isolated from waterfall sediment was tested for its decolorization. The identification of culturable bacteria by 16S rDNA based approach showed that the consortium composed of Klebsiella oxytoca, Serratia mercescens, Citrobacter sp. and unknown bacterium. In the context of academic study, prevention on the difficulties of providing effluent as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
1
24
0
2
Order By: Relevance
“…The pH values in this study were in line with the work of other authors [13][14][15] who found the pH of distillery wastewater relatively acidic (3.3 -3.9 and 3.8 -4.5, respectively). The low pH of the distillery effluent is due to the presence of higher concentration of organic acids such as CH3COOH formed during biochemical conversion of highly biodegradable organic matter [16,17] resulting from high BOD and COD loading (Table 3).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The pH values in this study were in line with the work of other authors [13][14][15] who found the pH of distillery wastewater relatively acidic (3.3 -3.9 and 3.8 -4.5, respectively). The low pH of the distillery effluent is due to the presence of higher concentration of organic acids such as CH3COOH formed during biochemical conversion of highly biodegradable organic matter [16,17] resulting from high BOD and COD loading (Table 3).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The exception is the study of Jiranuntipon et al (2008), who attempted to decolourize cane molasses vinasse, sugar beet molasses vinasse, caramel and Viandox sauce. These substances, depending on the variant, accounted for 20%; 41.5%; 30% and 13.5% v/v of culture medium for bacteria consortium obtained from waterfall sediments (pH0=4.0, T=30°C).…”
Section: Resultsmentioning
confidence: 99%
“…In the work presented in this study the reduction of caramel -coloured component of BMV was also at the lowest level of 6% and, in the case of using a mixed culture of lactic acid bacteria there was even an increase of these compounds in the medium (data not shown). This phenomenon can be explained by the high process temperature, high acidity, high osmotic pressure and high specific gravity caramel (Belitz et al, 2004;Chung et al, 1999;Jiranuntipon al., 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bharagava et al, 2009); Klebsiella oxytoca, Serratia mercescens and Citrobacter sp. (Jirianuntipon et al, 2008); Pseudomonas aeruginosa PAO1, Stenotrophomonas maltophila, and Proteus mirabilis (Mohana et al, 2007); Bacillus thuringiensis (MTCC 4714), Bacillus brevis (MTCC 4716) and Bacillus sp. (MTCC 6506) (Kumar and Chandra, 2006); Pseudomonas putida, Aeromonas sp.…”
Section: Introductionmentioning
confidence: 99%